1996
DOI: 10.1051/aas:1996155
|View full text |Cite
|
Sign up to set email alerts
|

Surface photometry of galaxies in low density regions

Abstract: Abstract. -We perform detailed surface photometry, based on B-and/or R-band CCD images of 92 faint galaxies. They are a subsample of those galaxies which were studied by Hopp et al. (1994) in the direction of three nearby voids. We derive integral photometric parameters and radial surface brightness profiles and compare them to those of several faint galaxy samples, located in different environments, and of a bright field galaxy sample. According to the obtained photometric characteristics, our sample is a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…The filter strength, defined by the minimum signal to noise ratio for the detection of a local signal, was generally between 2.0 − 2.5 σ, where σ is the rms noise level of the sky background at each scale length. After the filtering, a careful sky background level determination and subtraction was performed on the smoothed frame, as described in more detail in Vennik et al (1996). After the background subtraction the galaxy image was extracted from the large CCD frame and interactively cleaned from disturbing objects like e.g.…”
Section: Data Reduction and Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The filter strength, defined by the minimum signal to noise ratio for the detection of a local signal, was generally between 2.0 − 2.5 σ, where σ is the rms noise level of the sky background at each scale length. After the filtering, a careful sky background level determination and subtraction was performed on the smoothed frame, as described in more detail in Vennik et al (1996). After the background subtraction the galaxy image was extracted from the large CCD frame and interactively cleaned from disturbing objects like e.g.…”
Section: Data Reduction and Filteringmentioning
confidence: 99%
“…As a result, a sample of galaxies of late morphological type and of low surface brightness was identified, with several very isolated galaxies and galaxies populating the rims of the voids. Vennik et al (1996) performed B and R surface photometry of a subsample of these galaxies and concluded that both isolated and non-isolated galaxies show similar photometric and structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In the Hopp et al sample in the direction of voids only nine dwarf galaxies are located fully within voids (three objects), or in some intermediate regions near the void boundaries (six galaxies). These galaxies were observed in the H i 21 cm line by Huchtmeier et al (1997) (hereafter HHK) and their morphology and colors were studied by Vennik et al (1996). In the sample of Popescu et al there were also 17 void BCGs (eight fully located in voids), but these were not observed in H i.…”
Section: Introductionmentioning
confidence: 96%
“…Early papers include Andredakis, Peletier, & Balcells (1995), Schwarzkopf & Dettmar (1997), Seigar & James (1998), Iodice, D'Onofrio, & Capaccioli (1997, Khosroshahi, Wadadekar, & Kembhavi (2000), D'Onofrio (2001), Graham (2001a), Möllenhoff & Heidt (2001), and Prieto et al (2001). In either case, since the work of Capaccioli in the late 1980s and in particular Caon, Capaccioli, & D'Onofrio (1993) and D'Onofrio, , the past decade has seen an explosion in the application of the R 1/n model (e.g., Cellone, Forte, & Geisler 1994;Vennik & Richter 1994;Young & Currie 1994Graham et al 1996;Karachentseva 1996;Vennik et al 1996, to mention just a few early papers), yet no single resource exists for the expressions and quantities pertaining to the R 1/n model. Moreover, no one reference provides more than a few of the relevant equations, and many textbooks still only refer to the R 1/4 model.…”
Section: Introductionmentioning
confidence: 99%